Log Linier Binomial Negatif dalam Memodelkan Data Siswa Putus Sekolah Tingkat SMA/SMK - Santi, Vera Maya; Fanya Izmi Hawa; Bagus Sumargo (LPPM Universitas Negeri Jakarta, 2023)
Log linear negative binomial model is an extension of the linear regression model that can be used to analyze count data in the form of a contingency table when dealing with overdispersion where the variance value is greater than the mean value. Research in the field of education often produces contingency table data, one of which is data on students dropping out of school. The 2018 BPS survey showed that the number of students dropping out of school at the secondary school level in West Java province had the highest number of dropouts. Unfortunately, quantitative research on dropout students is still rarely done. Log linear negative binomial model is applied to determine the factors that influence the number of SMA/SMK dropout students in West Java province in 2021. The results show that gender, type of middle school, school status, interaction of gender and school status, and the interaction of middle school type and school status significantly affects the number of students dropping out of school. Furthermore, SMA/SMK dropouts in the province of West Java are dominated by male students, vocational students, and public-school students. Females are 1% more risky to drop out than males in public schools, while males are 1% more risky to drop out than females in private schools. SMA students are 59% more risky to drop out than SMK students in public schools, while SMK students are 71% more risky to drop out than SMA students in private school.